2010
DOI: 10.1359/jbmr.090812
|View full text |Cite
|
Sign up to set email alerts
|

Defects in mesenchymal stem cell self-renewal and cell fate determination lead to an osteopenic phenotype in Bmi-1 null mice

Abstract: In parathyroid hormone-related protein 1-84 ] knockin mice, expression of the polycomb protein Bmi-1 is reduced and potentially can mediate the phenotypic alterations observed. We have therefore now examined the skeletal phenotype of Bmi-1 À/À mice in vivo and also assessed the function of bone marrow mesenchymal stem cells (BM-MSCs) from Bmi-1 À/À mice ex vivo in culture.Neonatal Bmi-1 À/À mice exhibited skeletal growth retardation, with reduced chondrocyte proliferation and increased apoptosis.Osteoblast num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(149 citation statements)
references
References 51 publications
10
134
1
Order By: Relevance
“…Recently, reduced proliferation and increased apoptosis in bone marrow MSCs were associated with upregulation of p27. (28) We measured the expression of p27, and we could clearly observe that its regulation strictly followed the expression of p21. p27 was specifically inhibited by the RUNX2 siRNA.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, reduced proliferation and increased apoptosis in bone marrow MSCs were associated with upregulation of p27. (28) We measured the expression of p27, and we could clearly observe that its regulation strictly followed the expression of p21. p27 was specifically inhibited by the RUNX2 siRNA.…”
Section: Discussionmentioning
confidence: 92%
“…(38) As a consequence, Bmi-1 through inhibition of p16, p19, and p27 maintained self-renewal capacity of BM-MSCs and promoted their differentiation into osteoblasts, while inhibiting their differentiation into adipocytes. In previous studies, we found that the expression of Bmi-1 in Pthrp KI mouse bone tissue was significantly reduced and its nuclear translocation was significantly reduced.…”
Section: Discussionmentioning
confidence: 94%
“…Calcein double-labeling was performed by i.p. injection of calcein (10 mg/g body weight; C-0875; Sigma-Aldrich) at 6 and 1 days prior to sacrifice, as described previously (59). Bones were harvested and embedded in LR White acrylic resin.…”
Section: Methodsmentioning
confidence: 99%